Relation between socio-demographic factors and professionalism among nurses in Saudi Arabia: A comparative analysis - Hussein Alshumrani; Bander Albagawi; Sandro Villareal; Benito Areola Jr; Hamdan Albaqawi; Saleh Algamdi; Abdulrahman Alerwi; Ahmed Saad Altheban; Seham Alanazi (Belitung Nursing Journal, 2022)
Background: Analyzing how nurses handle professionalism in their careers will help all concerned individuals identify areas of concern to develop and enhance further to achieve or maintain a high degree of professionalism. Objective: This study aimed to determine the level of professionalism among nurses and its differences according to socio-demographic characteristics. Methods: A quantitative cross-sectional approach was utilized in three significant regions of Saudi Arabia. A simple random sampling technique was employed with 305 respondents, resulting in a 95.9% response rate. A Google Form survey was used to collect the data between January and April 2021. Results: Nurses perceived themselves highly in professional organization (Mean = 3.94, SD = 0.17), belief in public service (Mean = 3.91, SD = 0.22), belief in self-regulation (Mean = 3.97, SD = 0.08), sense of calling (Mean = 4.01, SD = 0.13), and belief in autonomy (Mean = 3.71, SD = 0.15). There was no significant difference between gender and professional organization, belief in public service, self-regulation, or belief in autonomy. Still, there was a significant difference in belief in public service (t = 2.794; p = 0.006) and sense of calling (t = 4.290; p = 0.001). As to age, only belief in self-regulation was significant (t = 5.984; p = 0.003). Moreover, the educational qualifications reached an insignificant difference in professionalism. Conversely, the type of facility has been found to have reached significant differences with a professional organization (F = 3.057; p = 0.029), belief in public service (F = 4.130; p = 0.007), beliefs in regulation (F = 3.452; p = 0.017), sense of calling (F = 3.211; p = 0.023), and belief in autonomy (F = 5.995; p = 0.001). Lastly, the current position found no significant difference in professionalism. Conclusion: Nurses in the Kingdom of Saudi Arabia perceived themselves as highly professional, and male nurses were found to have a sense of calling more than their female counterparts. Age, educational qualification, and current position had no significant difference in professionalism. Conversely, the type of facility had a significant difference with the belief in autonomy. These findings support and sustain the role of nurses in this 21st-century health care that is significantly needed to provide the most quality care.